Notes and descriptions on North American Desmiphorini (Coleoptera, Cerambycidae, Lamiinae) - Heffern, Daniel; Santos-Silva, Antonio (Zootaxa, 2017)
The differences between Estoloides Breuning, 1940, Tigrinestola Breuning, 1949, and Pseudestoloides Breuning & Heyrovsky, 1961 are discussed. A lectotype for Lypsimena tigrina Skinner, 1905 is designated. A new genus and two new species are described from Mexico: Tigrinestola nearnsi sp. nov., and Allotigrinestola sundbergi, gen. nov., sp. nov. A key to the four genera treated in this work, as well as to species of Tigrinestola are presented.